2007
DOI: 10.1016/j.cell.2007.05.014
|View full text |Cite
|
Sign up to set email alerts
|

A Microenvironment-Induced Myeloproliferative Syndrome Caused by Retinoic Acid Receptor γ Deficiency

Abstract: Myeloproliferative syndromes (MPS) are a heterogeneous subclass of nonlymphoid hematopoietic neoplasms which are considered to be intrinsic to hematopoietic cells. The causes of MPS are largely unknown. Here, we demonstrate that mice deficient for retinoic acid receptor gamma (RARgamma), develop MPS induced solely by the RARgamma-deficient microenvironment. RARgamma(-/-) mice had significantly increased granulocyte/macrophage progenitors and granulocytes in bone marrow (BM), peripheral blood, and spleen. The M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
386
2
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 485 publications
(406 citation statements)
references
References 42 publications
15
386
2
3
Order By: Relevance
“…We have previously reported that RARc germ line knock out mice (Rarg À/À mice) develop a non-haematopoietic cell intrinsic (microenvironmental) induced myeloproliferative disorder (Walkley et al, 2007). Analysis of the combined roles of RARa and RARc, the most highly expressed RARs in erythropoiesis, has not been possible due the lethality of compound null mutants.…”
mentioning
confidence: 99%
“…We have previously reported that RARc germ line knock out mice (Rarg À/À mice) develop a non-haematopoietic cell intrinsic (microenvironmental) induced myeloproliferative disorder (Walkley et al, 2007). Analysis of the combined roles of RARa and RARc, the most highly expressed RARs in erythropoiesis, has not been possible due the lethality of compound null mutants.…”
mentioning
confidence: 99%
“…Several studies found that deletion or mutation of functional genes in these niche cells led to MPNs, myelodysplasia, or leukemia [12,[28][29][30][31][32]. These findings and accordingly raised concepts were proved by the clinical transplantation investigations, in which donor-derived hematologic malignancies after hematopoietic stem cell transplantation were diagnosed [33].…”
Section: Oncogenesis In Abnormal Nichesmentioning
confidence: 70%
“…In an early elegant study, mice with deficiency of retinoic acid receptor gamma (RARγ) develop Myeloproliferative neoplasms (MPNs) characterized by significantly increased granulocyte/macrophage progenitors and granulocytes in BM, peripheral blood, and spleen. Interestingly, BM from wild-type mice transplanted into the RARγ-deficient microenvironment rapidly developed the MPNs, indicating that the disorder was not intrinsic to hematopoietic cells and thus demonstrating the possibility that alterations of the microenvironment as a sole cause of hematopoietic neoplasms [28]. In a parallel study, mice with combined loss of Retinoblastoma (RB) in both hematopoietic cells and microenvironment could develop MPN, indicating that the disease resulted from an interaction between blood cells and the altered microenvironment [12].…”
Section: Oncogenesis In Abnormal Nichesmentioning
confidence: 99%
“…De plus, on ne peut exclure que des altérations géniques de CSM puissent favoriser le développement de certains cancers comme cela a été suggéré pour les cellules stromales composant la niche hématopoïétique dans le cas de certaines leucémies [30][31][32]. Ce champ d'investigation très actif aujourd'hui permettra d'envisager les potentialités et les écueils de l'utilisation des CSM dans le traitement des cancers, mais aussi le rôle des CSM endogènes dans le développement tumoral.…”
Section: Resultsunclassified